Dynamic compressive behavior of freeze–thaw damaged roller-compacted concrete and establishment of constitutive model. (15th February 2023) - Du, Xiaoqi; Si, Zheng; Li, Yanlong; Huang, Lingzhi; Si, Zhibo; Wen, Lifeng
Highlight: The threshold of freeze–thaw damage of RCC was determined. The dynamic response of freeze–thaw damage RCC was analyzed by the combination of theory and experiment. Establishment of dynamic compression constitutive model for freeze–thaw RCC. Abstract: Roller-compacted concrete (RCC) structures are frequently subjected to the combined effects of freeze–thaw (FT) damage and dynamic loads in cold and earthquake-prone areas, resulting in a decrease in the mechanical properties of RCC. In this paper, the mechanical properties of RCC under the combined action of FT damage and dynamic compression were studied through physical tests, and the dynamic compression constitutive model of freeze–thaw RCC (FTRCC) was established based on Weibull-Lognormal model. The results showed that 75 cycles were the threshold of FT damage of RCC, beyond which the relative dynamic elastic modulus (RDEM) decreases rapidly and the pores increases significantly. At the same strain rate, the dynamic compressive strength of RCC presents three different stages with the increasing of FT cycles: (I) slow decline (II) decline (III) rapid decline. The dynamic compressive strength of RCC increased with the increasing of strain rate under the same FT cycles. Meanwhile, the failure pattern of the specimen changed significantly. The variation law of mechanical properties of RCC under any FT cycles and strain rates can be quickly determined using the established dynamic constitutive model of FTRCC and the static compressive mechanical parameters of RCC under normal state. It can offer a theoretical support for assessing the dynamic mechanical behavior of RCC in cold and earthquake-prone areas.